Kendala Kerjasama Sister City Antara Kota Semarang dengan Kota Jung-Gu Tahun 2016 – 2021 - Nisa Ristadina (Journal of International Relations, 2023)
Sister city cooperation appears as a form of paradiplomacy where the actor is the local government. Sister city cooperation between Semarang City and Jung-Gu City has been established since 2016 with five points of agreement. However, after five years, the cooperation between the two has not gone well. This study aims to explain the obstacles to sister city collaboration between the City of Semarang and the City of Jung-Gu from 2016 – 2021 by using the concept of paradiplomacy and the concept of sister city. This study uses a qualitative research approach with explanatory research types and data obtained through interviews and literature studies. The results of this study indicate that the factors that cause sister city cooperation between Semarang City and Jung-Gu City have not gone well in several areas that have been agreed upon because both of them do not fulfill three of the five important elements needed to assess the success of inter-city cooperation. Some of these elements are the commitment of the two parties to cooperation, community participation in cooperation, and reciprocal relations between cities.